Bootstrap Hypothesis Testing - James G. MacKinnon (Queen's University, Department of Economics, 2007)
This paper surveys bootstrap and Monte Carlo methods for testing hypotheses in econometrics. Several different ways of computing bootstrap P values are discussed, including the double bootstrap and the fast double bootstrap. It is emphasized that there are many different procedures for generating bootstrap samples for regression models and other types of model. As an illustration, a simulation experiment examines the performance of several methods of bootstrapping the supF test for structural change with an unknown break point.
Keywords: C12; C15; 330; bootstrap test; supF test; wild bootstrap; pairs bootstrap; moving block bootstrap; residual bootstrap; bootstrap P value; Ökonometrie; Statistischer Test; Bootstrap-Verfahren; Monte-Carlo-Simulation